Unbecoming Language Anti-Identitarian French Feminist Fictions - Kim, Annabel (The Ohio State University Press, 2018)
In Unbecoming Language, Annabel L. Kim examines a corpus of French literature writing against difference. Inaugurated by Nathalie Sarraute and sustained in the work of Monique Wittig and Anne Garréta, this corpus highlights three generations of the twentieth and recent twenty-first centuries and the direct chain of influence between them. Kim considers these writers, and the story of literature's political potential, as a way of rereading and reinterpreting each writer's individual corpus-rearticulating the strain of anti-difference feminist thought that has been largely forgotten in our (Anglo-American) histories of French feminisms.